Portuguese Origins of a 16th Century Aqueduct in México - Doolittle, William E. (Revista Geográfica de América Central., 2018)
Many aqueducts built during the Spanish colonial era remain standing in México, albeit not functioning. A few date to the 16th century. Some of these early aqueducts are quite spectacular and highly visible. Others are small and are located in places not easily found. Despite their size, small aqueducts are important for understanding knowledge pertaining to technology transfers from the Old World to the New. One such aqueduct is on the property of the Hacienda de Pacho, near Xalapa in the state of Veracruz. One of its highly unusual characteristics is that its construction involved Gothic arches. No other colonial aqueduct in México has such features. According to documentary courses dating to AD 1591, it was built by the hacienda’s original owner who was from the Portuguese island of Madeira. This paper reports on field activities involved in verifying the Maderian origins of this unique aqueduct.